The Optimization of Essential Oil Extraction from Java Cardamom - Raissa Raissa; Windi Cahya Amalia; Meri Ayurini; Khabib Khumaini; Paramita Jaya Ratri (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2020)
Indonesia is one of the largest spice-producing regions such as the Java Cardamom (Amomum compactum). The cardamom can be converted into derivative products in the form of cardamom essential oil. In this work, we attempted to extract the essential oil from the cardamom by comparing two methods of extraction which are the steam distillation and the simple distillation. The optimization factors considered on the extraction yield were solvent (ethyl acetate and n-hexane) and extraction time (3-6 h). The extraction yield obtained by both methods in ethyl acetate solvents was almost equal to that obtained in n-hexane. Also, the result obtained revealed that the extraction yield increased with time. The optimum essential oil yield was obtained by the simple distillation method in 6 hours duration time using n-hexane solvent giving the yield of 6.3 %. Gas Chromatography-Mass Spectrometry (GC-MS) was used to identify the chemical composition of the extracted oil. The results showed that the chemical composition of the essential oils is different in each extraction time. The main compounds in all oil samples were eucalyptol and camphene among four other constituents. The concentration of eucalyptol reached an optimum (90.89 - 93.74 %) at 4 – 5 h of distillation times, while the concentration of camphene reached an optimum (52.98 %) at 6 h. The purity of the essential oil was confirmed by Fourier Transform Infra-Red (FTIR). Moreover, this research will help to utilize the cardamom due to its main compounds that act as herbal medicine.